Assessment of the feed additive consisting of taurine (3a370) for Canidae, Felidae, Mustelidae and carnivorous fish for the renewal of its authorisation and the request for a new use in all poultry and all porcine species (Regal B. V.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of taurine as a nutritional feed additive (functional group: vitamins, pro‐vitamins and chemically well‐defined substances having similar effect) for the renewal of its authorisation for use in Canidae, Felidae, Mustelidae and carnivorous fish and for the new use in the same category (functional group: amino acids, their salts and analogues), in all poultry and all porcine species. The FEEDAP Panel concludes that taurine remains safe under the current conditions of authorisation for Canidae, Felidae, Mustelidae and carnivorous fish, consumer and environment. The Panel also concludes that levels up to 0.2%, with no margin of safety, are tolerated in all poultry and all porcine species, for which the new use of taurine as an amino acid is requested. The FEEDAP Panel concludes that the additive is a skin and eye irritant, and a skin and respiratory sensitiser and that any exposure is considered a risk. There is no need for the assessment of the efficacy of the additive in Canidae, Felidae, Mustelidae and carnivorous fish in the context of the renewal of the authorisation. The Panel concludes that taurine cannot be considered a nutritional additive for all poultry and porcine species.